Pengaruh Model Pembelajaran terhadap Hasil Belajar Passing Control Sepak Bola ditinjau dari Motivasi Belajar - yusdika, I kadek; Wahjoedi, H. Wahjoedi; Sudiana, I Kt.; Parwata, I G. Lanang Agung; Yoda, I Kt. (DEPARTEMEN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2024)
This research aims to determine: (1) Differences in football passing control learning outcomes between students who follow the PBL and STAD learning models. (2) The interaction between learning motivation and learning model on football passing control learning outcomes. (3) Differences in football passing control learning outcomes between students who have high learning motivation and low learning motivation in the PBL and STAD learning models. This type of research is quasi-experimental with a 2x2 treatment by level design. The research population was 328 class VIII students at SMP Negeri 6 Singaraja. The total sample in this study was 84 people selected using simple random sampling technique. The data analysis technique used was two way ANOVA followed by the Tukey test. This research shows that, (1) There is a significant difference in learning outcomes for football passing control between students who follow the PBL and STAD learning models (F= 20.477, sig. p 0.000˂0.05). (2) There is a significant interaction between learning motivation and learning model on football passing control learning outcomes (F=16.782, sig. p 0.00˂0.05). (3) There is a significant difference in learning outcomes for football passing control between students who follow the PBL and STAD learning models who have high learning motivation (F= 28, 785, sig. p 0.000˂0.05). (4) There is a significant difference in learning outcomes for football passing control between students who follow the PBL and STAD learning models who have low learning motivation (F= 5.950, sig. p 0.019˂0.05). It can be concluded that the PBL learning model and the STAD learning model influence the learning outcomes of football passing control in terms of learning motivation